Pembuatan Pangkalan Data Arsip Menggunakan Microsoft Access pada Seksi Pemberitaan di LPP RRI Bukittinggi - Oktaviani, Anggie Hamdia; Nelisa, Malta (Ilmu Informasi Perpustakaan dan Kearsipan, 2015)
The aims of this study was to describe about how to make a database archive in order to help the employers of Seksi Pemberitaan in LPP RRI Bukittinggi in finding news archive immediately, quickly, and accurately. Besides, it can helps to safe storage. The instrument of this study is qualitative research. The technique of data collection is direct observation method to seksi Pemberitaan in the LPP RRI Bukittinggi. In addition, the technique of data collection is interview method to head seksi pemberitaan and newscaster of LPP RRI Bukittinggi. This study uses daily news. Based on discussion above, it can be concluded that making database as a tool to find archive quickly in Seksi Pemberitaaan LPP RRI Bukittinggi by using Microsoft Access 2010 based on table. The table consists of field, query, form, and report. The query is a table to change data. The table form is a form table that used to find a data. The table report as final result of this study in making database archive. The switchboard are able to help the user to give direction to find database archive. Keyword: Database, electronic archives